2019
DOI: 10.1111/1365-2656.13086
|View full text |Cite
|
Sign up to set email alerts
|

Females facilitate male food patch discovery in a wild fish population

Abstract: 1. Responding to the information provided by others is an important foraging strategy in many species. Through social foraging, individuals can more efficiently find unpredictable resources and thereby increase their foraging success.2. When individuals are more socially responsive to particular phenotypes than others, however, the advantage they obtain from foraging socially is likely to depend on the phenotype composition of the social environment. We tested this hypothesis by performing experimental manipul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 79 publications
4
27
1
Order By: Relevance
“…In our earlier work with wild Trinidadian guppies living upstream in resource-poor environments, we revealed that more social individuals located more novel food patches [21,41], suggesting that sociality plays a relevant role in resource detection in this population. Due to the lack of predators [42] and the infrequent use of aggression [21] in our population, we did not expect a strong increase or decrease in resource acquisition with conspecific number. Previous work showed that male guppies are generally less social [21,[43][44][45][46][47] and more risk-taking than females [43,[48][49][50].…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…In our earlier work with wild Trinidadian guppies living upstream in resource-poor environments, we revealed that more social individuals located more novel food patches [21,41], suggesting that sociality plays a relevant role in resource detection in this population. Due to the lack of predators [42] and the infrequent use of aggression [21] in our population, we did not expect a strong increase or decrease in resource acquisition with conspecific number. Previous work showed that male guppies are generally less social [21,[43][44][45][46][47] and more risk-taking than females [43,[48][49][50].…”
Section: Introductionmentioning
confidence: 62%
“…Experimental fish were caught from a nearby stretch of the same river and were, upon capture, sexed (194 females, 143 males), sized (females: Mean ± SD = 24.6 ± 3.7 mm, males: Mean ± SD = 21.6 ± 1.6 mm) and individually marked using Visible Implant Elastomer (VIE) tags (©Northwest Marine Technology Inc.) [21,46,53].…”
Section: Materials and Methods (A) Study Systemmentioning
confidence: 99%
See 3 more Smart Citations